Sexti Properti Elegi - Heyworth, S. J. (Scriptorum classicorum bibliotheca Oxoniensis., 2007)
A radical new edition of the Augustan poet Propertius, based on the latest research into the manuscript tradition. The English preface contains important comments on the way texts are edited and read. Some important emendations discovered in the papers of A. E. Housman are published here for the first time. - ;Propertius is a poet of the Augustan period, a successor of the great Hellenistic elegiac poets Callimachus and Philitas, and a precursor of Ovid. His account of his fictionalized affair with his beloved alter ego Cynthia is the purest expression of the spirit of love elegy, setting them.